Preparation method of concrete recycled aggregate

The coal gangue is refined through ball milling and screening treatment, and emulsifier and water glass are added to the wet ball mill. Combined with freezing and pressing treatment, the problems of uneven porosity and particle distribution of coal gangue are solved, and the performance stability of concrete is improved and durability, achieving a more uniform product quality.

CN119263675AInactive Publication Date: 2025-01-07HANYUAN HENGXIANG TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411439449.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When coal gangue is used as a concrete recycled aggregate, due to its large porosity and uneven distribution, it leads to unstable concrete performance, affecting construction performance and mechanical properties, and may trigger chemical reactions and reduce durability.

Method used

Coal gangue is refined through ball milling and screening treatment, and emulsifier and water glass are added during the wet ball milling process to promote the reaction of water glass, reduce porosity and surface defects, modify the surface of particles, and form regular particle shape and size distribution. Combined with freezing and pressing treatment to broaden the pores and improve the ball milling effect.

Benefits of technology

It significantly reduces the porosity and cracks of coal gangue, improves the regularity and uniformity of particles, enhances the construction and mechanical properties of concrete, improves compressive strength and durability, and reduces the consumption of water glass.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of building materials. The invention relates to the field of concrete, in particular to a preparation method of concrete recycled aggregate. The preparation method comprises the following specific preparation steps: carrying out ball milling and mixing on coal gangue, and screening to obtain refined coal gangue with D50 of 3-5mm; the preparation method comprises the following steps: mixing 100-120 parts by weight of refined coal gangue, 3-5 parts by weight of an emulsifier and 80-100 parts by weight of water glass, pouring the mixture into a ball milling tank, carrying out wet ball milling reaction for 4-6 hours, discharging, filtering, washing, drying, scattering, roasting at low temperature, cooling and discharging to obtain the concrete recycled aggregate. Wherein the wet ball-milling reaction comprises the following steps: adding ball-milling beads according to the mass ratio of (32-35): 1 at room temperature, and carrying out wet ball-milling reaction under the conditions that the autorotation speed is 350-370r / min and the revolution speed is 220-230r / min; the low-temperature roasting comprises low-temperature roasting for 3-4 hours under the condition that the temperature is 185-190 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of building materials, and more specifically, relates to a method for preparing recycled concrete aggregate. Background Art

[0002] The raw materials used as recycled aggregates for concrete mainly include:

[0003] Waste concrete and construction waste: This is the main source of recycled aggregate, including concrete fragments recovered from demolished buildings, roads, bridges and other structures. Industrial waste residue: such as fly ash, coal gangue, tailings, smelting slag, industrial by-product gypsum, etc. These materials can be used as auxiliary raw materials for recycled aggregate and can sometimes be used to replace part of cement.

[0004] For the above raw materials, when coal gangue is used as the raw material for recycled aggregate in concrete, the following technical problems may arise:

[0005] High porosity and water absorption: Gangue has high porosity and high water absorption, which may reduce the free water content of fresh concrete, causing fresh concrete to be dry and thick, with poor fluidity, affecting the construction performance of concrete. High crushing value: Gangue contains certain soft rocks, residual coal, organic matter and other substances, which are oxidized during the combustion process, causing the chemical composition and structure of the gangue to change, the porosity to increase, and the aggregate to become loose, so it is easy to be crushed, affecting the mechanical properties of concrete. Strength and durability issues: The strength of gangue concrete may be lower than that of ordinary concrete, and its durability, such as frost resistance and impermeability, may be poor. The high water absorption of gangue aggregate may cause rapid loss of water inside the concrete, affecting the hydration reaction of cement, thereby reducing the strength and durability of concrete. Interface bonding problem: The bonding between gangue aggregate and cement paste may not be as good as that of natural aggregate, which may affect the overall performance of concrete. Chemical reaction problems: Gangue may contain harmful components such as sulfides, which may cause expansion or other chemical reactions in concrete, affecting the performance of concrete. Particle shape and size distribution problems: The particles of crushed gangue may have irregular shapes and uneven size distribution, which may affect the workability and mechanical properties of concrete. Summary of the invention

[0006] The technical problem to be solved by the present invention is: in view of the prior art, when coal gangue is used to prepare recycled aggregate for concrete, due to its large porosity and uneven distribution, and during the processing, it is difficult to ensure its regular properties and uniform size, which leads to the instability of concrete performance and the difficulty in controlling product quality. The present invention provides a method for preparing recycled aggregate for concrete.

[0007] The purpose of the invention is to provide a method for preparing recycled concrete aggregate.

[0008] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0009] A method for preparing recycled concrete aggregate, the specific preparation steps comprising:

[0010] After the coal gangue is ball-milled and mixed, it is sieved to obtain fine coal gangue with a D50 of 3-5 mm;

[0011] First, the ball milling process is used to screen out the fine coal gangue with a particle size of corresponding specifications. In the ball milling process, the edges and corners of the coal gangue can be removed by the action of the ball milling beads, and the defects in the structure of the coal gangue, such as micropores and cracks, can be effectively exposed, which is conducive to the formation of silicate deposits in the subsequent reaction process with water glass;

[0012] According to weight, take 100-120 parts of fine coal gangue, 3-5 parts of emulsifier, and 80-100 parts of water glass, mix and pour into a ball mill, wet ball mill reaction for 4-6 hours, discharge, filter, wash, dry and break up, low-temperature roast, cool, discharge, and obtain recycled aggregate for concrete;

[0013] The wet ball milling reaction comprises: adding ball milling beads at a ball-to-material mass ratio of 32-35:1 at room temperature, and performing wet ball milling reaction at a rotation speed of 350-370 r / min and a revolution speed of 220-230 r / min;

[0014] The low-temperature roasting comprises: low-temperature roasting at a temperature of 185-190° C. for 3-4 hours.

[0015] By introducing emulsifier and water glass in the above wet ball milling process, firstly, under the action of emulsifier, particles of different sizes can be always in a suspended state under the driving action of ball milling beads during the wet ball milling process, so as to participate in the ball milling process. In particular, fine particles can further modify and grind the surface of coal gangue under the physical action of ball milling beads to reduce surface defects. Secondly, under the action of emulsifier, water glass is also more likely to penetrate and diffuse into cracks and pores inside coal gangue. Among them, metal ions inside coal gangue diffuse and react with water glass to form substances such as calcium silicate, which are deposited in micropores and cracks on the surface and inside, reducing porosity to a certain extent and avoiding excessive water absorption in the concrete system to affect the hydration reaction of concrete. In addition, under the action of emulsifier, the proportion of harmful and irregular capillaries in coal gangue structure caused by water glass can be significantly reduced, and finally, a relatively regular coal gangue aggregate product with reduced pores and cracks is formed to obtain a homogenized coal gangue aggregate product.

[0016] Furthermore, the particle size distribution range of the refined coal gangue is 0.6-10 mm.

[0017] By increasing the number of screening times during the screening process, particles with a narrow particle size distribution range can be obtained, so that in the subsequent wet ball milling process, the properties of the raw materials are relatively uniform, avoiding the introduction of excessively fine or coarse particles, which would lead to excessive consumption of water glass or emulsifiers in the subsequent reaction process and affect the final effect of the reaction.

[0018] Furthermore, the emulsifier is selected from any one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium bromide, emulsifier OP-10, span-40, span-60, span-80, Tween-40, Tween-60, and Tween-80.

[0019] Furthermore, the modulus of the water glass is 1.25-1.45.

[0020] Furthermore, the specific preparation steps also include:

[0021] The gangue and water are mixed in a mass ratio of 1:5-7, filtered, and the filter cake is frozen at a temperature of -10-20°C for 8-12 hours, taken out, heated and dried to remove moisture, and the pretreated gangue is obtained;

[0022] By soaking in water before ball milling, water molecules can quickly diffuse and penetrate into the interior during the soaking process. Combined with the subsequent freezing process, the water molecules change from liquid to solid ice. In this process, the volume expands, so that the invisible channels inside can be effectively widened. This will be beneficial for the effective exposure of the weak points of the physical structure during the ball milling process, thereby fully refining it. At the same time, it will also be beneficial for the subsequent infiltration of water glass.

[0023] Then, the pretreated coal gangue is ball-milled and mixed, and then sieved to obtain refined coal gangue with a D50 of 3-5 mm;

[0024] According to weight proportions, take 100-120 parts of refined coal gangue, 3-5 parts of emulsifier, and 80-100 parts of water glass, mix and pour into a ball mill, wet ball mill reaction for 4-6 hours, discharge the material, filter, wash, dry and break up, low-temperature roast, cool, and discharge the material to obtain recycled concrete aggregate.

[0025] Furthermore, the specific preparation steps also include:

[0026] The gangue and water are mixed in a mass ratio of 1:5-7, filtered, and the filter cake is frozen at a temperature of -10-20°C for 8-12 hours, and then continuously squeezed at a pressure of 10-12MPa for 20-30 minutes, taken out, heated and dried to remove moisture, thereby obtaining pretreated gangue.

[0027] In the pretreatment process, after the freezing treatment, physical pressing treatment is further adopted, so that some pores or cracks can be broken along the direction of the ice crystals, which has a preliminary refinement effect, thus facilitating the subsequent ball milling process to obtain more uniform materials.

[0028] Furthermore, the specific preparation steps also include:

[0029] According to weight, 100-120 parts of refined coal gangue, 6-8 parts of spherical nano-silicon dioxide, 3-5 parts of emulsifier, and 80-100 parts of water glass are mixed and poured into a ball mill, and wet ball milled for 4-6 hours, and then discharged, filtered, washed, dried and broken up, low-temperature roasted, cooled, and discharged to obtain recycled aggregate for concrete;

[0030] The particle size distribution range of the spherical nano-silicon dioxide is 3-10 nm; and the sphericity of the spherical nano-silicon dioxide is 8.6-9.0.

[0031] The inventors found that if some spherical nano-silica with a relatively narrow particle size distribution range and relatively high sphericity is added, it can block some of the pores inside the coal gangue, thereby inducing the reaction products of water glass to begin to deposit at fixed positions in the pores of the coal gangue, and achieve fixed-point reinforcement of the pores, thereby avoiding excessive consumption of water glass. DETAILED DESCRIPTION

[0032] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0033] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0034] Example 1

[0035] The gangue and water are mixed in a mass ratio of 1:5, and then allowed to soak for 4 hours at room temperature, filtered, and the filter cake is collected. The filter cake is frozen at -10°C for 8 hours, and then continuously squeezed at a pressure of 10 MPa for 20 minutes, taken out, and heated and dried at 100°C to remove moisture, thereby obtaining pretreated gangue.

[0036] The pretreated coal gangue is then transferred into a ball mill, and zirconium oxide ball milling beads are added at a ball-to-material mass ratio of 20:1. The ball milling is continued for 30 minutes at a rotation speed of 300 r / min and a revolution speed of 180 r / min, and the material is discharged and sieved to obtain refined coal gangue with a D50 of 3 mm and a particle size distribution range of 0.6-10 mm.

[0037] According to the weight percentage, 100 parts of refined coal gangue, 6 parts of spherical nano-silicon dioxide, 3 parts of emulsifier, and 80 parts of water glass are mixed and poured into a ball mill. After wet ball milling for 4 hours, the material is discharged, filtered, washed, dried and broken up, low-temperature roasted, cooled, and discharged to obtain recycled aggregate for concrete;

[0038] Wherein, the particle size distribution range of the spherical nano-silicon dioxide is 3-10nm; and the sphericity of the spherical nano-silicon dioxide is 8.6;

[0039] The wet ball milling reaction comprises: adding ball milling beads at a ball-to-material mass ratio of 32:1 at room temperature, and performing wet ball milling reaction at a rotation speed of 350 r / min and a revolution speed of 220 r / min;

[0040] The low temperature roasting comprises: roasting at a temperature of 185° C. for 3 hours;

[0041] The emulsifier is selected from sodium lauryl sulfate;

[0042] The modulus of the water glass is 1.25.

[0043] Example 2

[0044] The gangue and water were mixed in a mass ratio of 1:6, and then allowed to soak for 4 hours at room temperature, and then filtered to collect the filter cake. The filter cake was frozen at -15°C for 10 hours, and then continuously squeezed at a pressure of 11MPa for 25 minutes, and then taken out and heated and dried at 100°C to remove moisture, thereby obtaining pretreated gangue.

[0045] The pretreated coal gangue is then transferred into a ball mill, and zirconium oxide ball milling beads are added according to a ball-to-material mass ratio of 20:1. The ball milling is continued for 30 minutes at a rotation speed of 300 r / min and a revolution speed of 180 r / min, and the material is discharged and sieved to obtain a refined coal gangue with a D50 of 4 mm and a particle size distribution range of 0.6-10 mm.

[0046] According to weight, 110 parts of refined coal gangue, 7 parts of spherical nano-silicon dioxide, 4 parts of emulsifier, and 90 parts of water glass are mixed and poured into a ball mill. After wet ball milling for 5 hours, the material is discharged, filtered, washed, dried and broken up, low-temperature roasted, cooled, and discharged to obtain recycled aggregate for concrete.

[0047] Wherein, the particle size distribution range of the spherical nano-silicon dioxide is 3-10 nm; and the sphericity of the spherical nano-silicon dioxide is 8.8;

[0048] The wet ball milling reaction comprises: adding ball milling beads at a ball-to-material mass ratio of 33:1 at room temperature, and performing wet ball milling reaction at a rotation speed of 360 r / min and a revolution speed of 225 r / min;

[0049] The low temperature roasting comprises: roasting at a temperature of 188° C. for 3.5 hours;

[0050] The emulsifier is selected from sodium dodecylbenzene sulfonate;

[0051] The modulus of the water glass is 1.3.

[0052] Example 3

[0053] The gangue and water were mixed in a mass ratio of 1:7, and then allowed to soak for 4 hours at room temperature, and then filtered to collect the filter cake. The filter cake was frozen at -20°C for 12 hours, and then pressed at a pressure of 12 MPa for 30 minutes, and then taken out and heated and dried at 100°C to remove moisture, thereby obtaining pretreated gangue.

[0054] The pretreated coal gangue is then transferred into a ball mill, and zirconium oxide ball milling beads are added at a ball-to-material mass ratio of 20:1. The ball milling is continued for 30 minutes at a rotation speed of 300 r / min and a revolution speed of 180 r / min, and the material is discharged and sieved to obtain refined coal gangue with a D50 of 5 mm and a particle size distribution range of 0.6-10 mm.

[0055] According to weight, 120 parts of refined coal gangue, 8 parts of spherical nano-silicon dioxide, 5 parts of emulsifier, and 100 parts of water glass are mixed and poured into a ball mill. After wet ball milling for 6 hours, the material is discharged, filtered, washed, dried and broken up, low-temperature roasted, cooled, and discharged to obtain recycled aggregate for concrete;

[0056] Wherein, the particle size distribution range of the spherical nano-silicon dioxide is 3-10nm; and the sphericity of the spherical nano-silicon dioxide is 9.0;

[0057] The wet ball milling reaction comprises: adding ball milling beads at a ball-to-material mass ratio of 35:1 at room temperature, and performing wet ball milling reaction at a rotation speed of 370 r / min and a revolution speed of 230 r / min;

[0058] The low temperature roasting comprises: roasting at a temperature of 190° C. for 4 hours;

[0059] The emulsifier is selected from Span-60;

[0060] The modulus of the water glass is 1.45.

[0061] Example 4

[0062] Compared with Example 1, this embodiment is different in that:

[0063] The gangue and water are mixed in a mass ratio of 1:5, and then allowed to soak for 4 hours at room temperature, and then filtered to collect the filter cake. The filter cake is frozen at -10°C for 8 hours, and then taken out and heated and dried at 100°C to remove moisture, thereby obtaining pretreated gangue;

[0064] The rest of the conditions remain unchanged.

[0065] Example 5

[0066] Compared with Example 1, this embodiment is different in that:

[0067] The coal gangue was not pretreated and was directly ball-milled to obtain refined coal gangue; the other conditions remained unchanged.

[0068] Example 6

[0069] Compared with Example 1, this embodiment is different in that:

[0070] Nano-silicon dioxide with a particle size distribution range of 0.2-20 nm and a sphericity of 8.0 is used to replace the spherical nano-silicon dioxide used therein, and other conditions remain unchanged.

[0071] Example 7

[0072] The difference between this embodiment and embodiment 1 is that no spherical nano-silicon dioxide is added, and other conditions remain unchanged.

[0073] Comparative Example 1

[0074] The gangue and water are mixed in a mass ratio of 1:5, and then allowed to soak for 4 hours at room temperature, filtered, and the filter cake is collected. The filter cake is frozen at -10°C for 8 hours, and then continuously squeezed at a pressure of 10 MPa for 20 minutes, taken out, and heated and dried at 100°C to remove moisture, thereby obtaining pretreated gangue.

[0075] According to weight, 100 parts of pretreated coal gangue, 6 parts of spherical nano-silicon dioxide, 3 parts of emulsifier, and 80 parts of water glass are mixed and poured into a reaction kettle. After reacting for 4 hours at a stirring speed of 300 r / min, the material is discharged, filtered, washed, dried and broken up, low-temperature roasted, cooled, and discharged to obtain recycled aggregate for concrete;

[0076] Wherein, the particle size distribution range of the spherical nano-silicon dioxide is 3-10nm; and the sphericity of the spherical nano-silicon dioxide is 8.6;

[0077] The low temperature roasting comprises: roasting at a temperature of 185° C. for 3 hours;

[0078] The emulsifier is selected from sodium lauryl sulfate;

[0079] The modulus of the water glass is 1.25.

[0080] The performance tests were performed on the products obtained in the above examples and comparative examples. The specific test methods and test results are as follows:

[0081] 300 parts by weight of the recycled concrete aggregate obtained in the above embodiments or comparative examples, 280 parts of 42.5# Portland cement, 80 parts of silica fume, 25 parts of fly ash, 30 parts of quartz powder, 25 parts of lignin sulfonate water reducing agent, and 150 parts of water were taken and stirred to obtain concrete slurry;

[0082] The obtained concrete slurry was cast into samples with a specification of 60 mm × 80 mm × 120 mm. After natural curing for 28 days, the compressive strength of each test block was tested using a YAW-300 type fully automatic pressure testing machine. The specific test results are shown in Table 1, wherein the concrete slurry corresponding to a single embodiment or comparative example was cast into 5 parallel test blocks in the above manner, and the corresponding compressive strength was tested, and the average value and the difference between the maximum value and the minimum value were calculated;

[0083] Average compressive strength / MPa Compressive strength difference / MPa Example 1 162.5 5.8 Example 2 163.1 6.0 Example 3 162.9 6.1 Example 4 158.8 6.9 Example 5 145.1 8.0 Example 6 148.2 7.6 Example 7 140.8 7.8 Comparative Example 1 144.4 12.8

[0084] It can be seen from the test results in Table 1 that when the product obtained by the present invention is applied to concrete, concrete with excellent performance can be obtained, and the performance difference between parallel samples is relatively small, so a more uniform product can be obtained.

[0085] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing recycled aggregate for concrete, characterized in that: The specific preparation steps include: After the coal gangue is ball-milled and mixed, it is sieved to obtain fine coal gangue with a D50 of 3-5 mm; According to weight, take 100-120 parts of fine coal gangue, 3-5 parts of emulsifier, and 80-100 parts of water glass, mix and pour into a ball mill, wet ball mill reaction for 4-6 hours, discharge, filter, wash, dry and break up, low-temperature roast, cool, discharge, and obtain recycled aggregate for concrete; The wet ball milling reaction comprises: adding ball milling beads at a ball-to-material mass ratio of 32-35:1 at room temperature, and performing wet ball milling reaction at a rotation speed of 350-370 r / min and a revolution speed of 220-230 r / min; The low-temperature roasting comprises: low-temperature roasting at a temperature of 185-190° C. for 3-4 hours.

2. The method for preparing recycled concrete aggregate according to claim 1, characterized in that: The particle size distribution range of the refined coal gangue is 0.6-10 mm.

3. The method for preparing recycled aggregate for concrete according to claim 1, characterized in that: The emulsifier is selected from any one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium bromide, emulsifier OP-10, span-40, span-60, span-80, Tween-40, Tween-60, and Tween-80.

4. The method for preparing recycled aggregate for concrete according to claim 1, characterized in that: The modulus of the water glass is 1.25-1.

45.

5. The method for preparing recycled aggregate for concrete according to claim 1, characterized in that: The specific preparation steps also include: The gangue and water are mixed in a mass ratio of 1:5-7, filtered, and the filter cake is frozen at a temperature of -10-20°C for 8-12 hours, taken out, heated and dried to remove moisture, and the pretreated gangue is obtained; Then, the pretreated coal gangue is ball-milled and mixed, and then sieved to obtain refined coal gangue with a D50 of 3-5 mm; According to weight proportions, take 100-120 parts of refined coal gangue, 3-5 parts of emulsifier, and 80-100 parts of water glass, mix and pour into a ball mill, wet ball mill reaction for 4-6 hours, discharge the material, filter, wash, dry and break up, low-temperature roast, cool, and discharge the material to obtain recycled concrete aggregate.

6. The method for preparing recycled aggregate for concrete according to claim 5, characterized in that: The specific preparation steps also include: The gangue and water are mixed in a mass ratio of 1:5-7, filtered, and the filter cake is frozen at a temperature of -10-20°C for 8-12 hours, and then continuously squeezed at a pressure of 10-12MPa for 20-30 minutes, taken out, heated and dried to remove moisture, thereby obtaining pretreated gangue.

7. The method for preparing recycled aggregate for concrete according to claim 1, characterized in that: The specific preparation steps also include: According to weight, 100-120 parts of refined coal gangue, 6-8 parts of spherical nano-silicon dioxide, 3-5 parts of emulsifier, and 80-100 parts of water glass are mixed and poured into a ball mill, and wet ball milled for 4-6 hours, and then discharged, filtered, washed, dried and broken up, low-temperature roasted, cooled, and discharged to obtain recycled aggregate for concrete; The particle size distribution range of the spherical nano-silicon dioxide is 3-10 nm; and the sphericity of the spherical nano-silicon dioxide is 8.6-9.0.